2011
DOI: 10.1590/s1516-35982011001100020
|View full text |Cite
|
Sign up to set email alerts
|

Prediction equations to estimate the demand of energy and crude protein for maintenance, gain and egg production for laying Japanese quails

Abstract: -The study was conducted to estimate requirements of energy and crude protein for maintenance, weight gain and egg production of Japanese quails in the period of 67 to 107 days of age. Two experiments were performed: one, to determine the requirements for maintenance of protein, and the other, for energy. Experiments were conducted in a completely randomized design with four dietary levels of offer and four replicates of six birds. The diets offered were: ad libitum (100%), 75%, 50%, and 25% consumption ad lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
0
6
0
7
Order By: Relevance
“…However, the values are consistent when analyzing animals in the same category [27,31] which were: 1.94 and 2.28 × body weight 0.75 . It can be observed that the net requirement of CP (g/bird/day) for gain, determined by the two techniques (CS and NB) and reported in the works of [18,[25][26][27][28][29][30][31] The values of requirement of CP (g/bird/day) estimated for egg mass production in laying hens and Japanese quails were, respectively, 0.301 × egg mass [26], and 0.258 × egg mass [18]. However, the irst one presents a lower requirement of amino acids and CP, evidencing that the greater requirement of quails is related to the higher maturity rate, that is, higher precocity [9][10][11].…”
Section: Crude Protein: Methodologies and Requirementmentioning
confidence: 87%
See 4 more Smart Citations
“…However, the values are consistent when analyzing animals in the same category [27,31] which were: 1.94 and 2.28 × body weight 0.75 . It can be observed that the net requirement of CP (g/bird/day) for gain, determined by the two techniques (CS and NB) and reported in the works of [18,[25][26][27][28][29][30][31] The values of requirement of CP (g/bird/day) estimated for egg mass production in laying hens and Japanese quails were, respectively, 0.301 × egg mass [26], and 0.258 × egg mass [18]. However, the irst one presents a lower requirement of amino acids and CP, evidencing that the greater requirement of quails is related to the higher maturity rate, that is, higher precocity [9][10][11].…”
Section: Crude Protein: Methodologies and Requirementmentioning
confidence: 87%
“…There studying the requirements of CP for maintenance and gain with Japanese quails in production using the CS technique, [18] It is known that nutritional needs are changed according to species, animal category, room temperature, diet composition and animal density. However, another important factor that changes the nutritional needs is the methodologies used [18,[25][26][27][28][29][30][31], such as the CS and NB techniques used in the elaboration of prediction equations.…”
Section: Crude Protein: Methodologies and Requirementmentioning
confidence: 99%
See 3 more Smart Citations